(untitled) (Journal of Pathology of Nepal, 2018)
Background: Gastrointestinal tract endoscopy along with biopsy is an established procedure for investigating a wide range of gastrointestinal conditions especially inflammatory and malignant diseases. The aim was to study and categorizing the morphological lesions of non-malignant origin at various sites of gastrointestinal tract and to compare with its endoscopic findings. Materials and Methods: This study was conducted on 280 benign GI biopsies received in the Department of Pathology of Sri Guru Ram Das Institute of Medical Sciences and Research, Amritsar, Punjab, India. Results: Maximum cases (39%) were observed in the age group of 41-60 years. Male patients outnumbered the females (male to female ratio was 1.4:1). There were total 33 esophageal biopsies amongst which the most common lesion was non-specific esophagitis with least common being Barrett’s esophagus. Correlating the results of endoscopic and histopathological features of acute and chronic gastritis a positive predictive value of 80% with sensitivity of 44.4% was seen. Total 83 duodenal biopsies were analyzed with non-specific duodenitis being the most commonly diagnosed lesion followed by celiac disease. Correlation of endoscopic and histopathological findings in celiac disease revealed a sensitivity of 50% and positive predictive value of 42.86%. In both sigmoid colon and rectum, non-specific colitis was the commonest diagnosis followed by ulcerative colitis. Endoscopic findings were correlated with the histopathological features in ulcerative colitis, revealing a sensitivity of 57.14% along with the positive predictive value of 80%. Conclusion: Histopathology remains the gold standard for diagnosing a case along with endoscopic findings and endoscopic findings alone cannot make the final diagnosis.